Predictors of presarcopenia in community-dwelling older adults: A 5-year longitudinal study. Issue 6 (2nd November 2019) - Kobayashi, Kazuyoshi; Ando, Kei; Tsushima, Mikito; Machino, Masaaki; Ota, Kyotaro; Morozumi, Masayoshi; Tanaka, Satoshi; Kanbara, Shunsuke; Ishiguro, Naoki; Hasegawa, Yukiharu; Imagama, Shiro
Abstract: Objectives : Sarcopenia is an aging-induced decrease in muscle mass that increases frailty and fall in elderly people. Presarcopenia corresponds to the preliminary stage of sarcopenia. The purpose of this prospective study is to examine predictors of presarcopenia in health screening. Methods: The subjects were 124 community residents aged ≥60 years (55 males, 69 females, average age 70.2 years) who attended local government health checkups in 2010 and 2015, as part of the Yakumo study, and did not have presarcopenia in 2010. Body mass index (BMI), waist and hip circumferences, grip strength, bone mineral density (BMD), 10-m gait time, back muscle strength, and stride length were measured. Presarcopenia was defined using the appendicular skeletal muscle index (arm and leg skeletal muscle mass/height 2 ). Results: The prevalences of presarcopenia in 2015 in males and females were 21.8% (12/55) and 30.4% (21/69), respectively. BMI, grip strength, BMD, back muscle strength, and osteoporosis deteriorated significantly more in the pre-sarcopenia group ( n = 33) compared with controls ( n = 91; no presarcopenia in 2015). In multivariate analysis, osteoporosis (OR 3.12, 95% CI 1.07-9.09; p < .05) was significantly associated with presarcopenia after 5 years. Conclusions: Establishment of risk factors for future pre-sarcopenia may allow development of evidence-based prevention strategies for this condition.